Prognostic factors in nonsmall cell lung cancer: insights from the German CRISP registry. Issue 2 (2nd February 2023) - Metzenmacher, Martin; Griesinger, Frank; Hummel, Horst-Dieter; Elender, Corinna; Schäfer, Harald; de Wit, Maike; Kaiser, Ulrich; Kern, Jens; Jänicke, Martina; Spring, Lisa; Zacharias, Stefan; Kaiser-Osterhues, Anja; et al.
Introduction: Understanding prognosis, especially long-term outcome, in advanced nonsmall cell lung cancer (NSCLC) is crucial to inform patients, guide treatment and plan supportive and palliative care. Methods: Prognostic factors influencing overall survival (OS) and progression-free survival (PFS) in 2082 patients with wild-type (WT)-NSCLC (629 M1a, 249 M1b, 1204 M1c) are reported. Patients were included in the prospective German CRISP registry recruiting in >150 centres. Analysis for pre-therapeutic factors was based on results from Cox proportional hazard models. Results: Current M-descriptors of the Union for International Cancer Control-8 staging system were validated: M1a and M1b patients had significantly longer median time to events compared to M1c (OS/PFS 16.4/7.2 months, 17.8/6.7 months and 10.9/5.4 months, respectively). OS and PFS were influenced by number and location of metastatic organ systems. M1c and four or more metastatic organs involved had shorter OS and PFS than M1c with one to three organs (OS hazard ratio (HR) 1.69, p<0.001; PFS HR 1.81, p<0.001). M1b-liver metastases had shorter OS/PFS than M1b involving other organs (OS HR 2.70, p=0.006; PFS HR 2.48, p=0.007). Based on number of involved organs (orgsys) and liver metastases, two risk groups (low-risk: M1a, M1b-non-liver, M1c-1-3-orgsys-non-liver; high-risk: M1c-liver, M1b-liver, M1c-4+-orgsys) with significantly different prognoses could be amalgamated (median OS/PFS 14.3/6.5 months and 7.7/4.1 months, respectively). Other favourable factors were female gender and Eastern Cooperative Oncology Group stage 0, with age showing no impact. Those with T1- or N0-status were associated with longer OS than T2–4 or N2–3. Conclusion: In this large observational dataset, we further defined factors for outcome in WT-NSCLC, including increased number of involved metastatic organ systems and liver metastases, as those with overall poorer prognosis and reduced survival chance. Advanced NSCLCs without driver mutations have inferior long-term survival once liver metastases or ≥4 metastatic sites are present. In patients with <4 metastatic organ sites, liver metastases also represent a negative prognostic factor. https://bit.ly/3Ui4v9m